Analisa SWOT Penggunaan QRIS pada Pemahaman Pengelolaan Keuangan: Studi Kasus Pelaku Usaha Mikro Sektor Makanan di Tropodo Sidoarjo - Zahra Adistya Saffanah; Riska Ayu Setiawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the SWOT of the application of the Quick Response Indonesian Standard (QRIS) in deepening the understanding of financial management in micro business actors in the food sector in Tropodo, Sidoarjo. The method used is qualitative descriptive with case studies, through in-depth interviews with five business actors who have adopted QRIS. The data was analyzed using source triangulation to ensure the validity of the findings. The results of the study show that QRIS provides strength in the form of ease of transactions, automatic recording, cash flow transparency, and increased consumer competitiveness. Weaknesses that arise include delays in disbursement of funds, deduction fees, mixing business funds with personal funds, and lack of understanding of advanced features. From the external side, opportunities are reflected in the trend of cashless society, digital financial literacy, integration with supporting applications, and the expansion of the cashless payment ecosystem. Meanwhile, threats include network disruptions, security risks, reliance on service providers, and potential data leaks. Overall, QRIS not only acts as a means of payment, but also as a strategic instrument for MSME financial governance. Therefore, it is important to increase financial literacy and infrastructure support so that the benefits of QRIS can be optimized.